Design and Evaluation of a Gamification-Based Mobile Application for Mandarin Vocabulary Learning for Beginners - Akbar Iskandar; Riska Kherani; Muhammad Akbar Azis; Yutaka Matsuo (Ceddi Journal of Education, 2025)
Vocabulary learning is the main foundation in mastering foreign languages, including Mandarin, which has a high level of complexity in terms of hanzi, pinyin, and lexical meaning. In Indonesia, the need for Mandarin mastery continues to increase along with the development of economic and academic cooperation with China. However, the process of learning Mandarin vocabulary for beginners is still dominated by conventional approaches that are less adaptive to the characteristics of digital-era learners. The contribution of this research lies in the design of a mobile application that integrates hanzi exercises, flashcard games, and a digital dictionary into a structured gamification mechanism based on levels, scores, and time limits for HSK 1–4 vocabulary learning. This study uses a quantitative descriptive method with a software engineering approach. Evaluation was conducted through direct trials with eight beginner learners using a five-point Likert scale questionnaire instrument. Data analysis was carried out using descriptive statistics and instrument reliability testing. The results showed an overall average score of 4.36 with a Cronbach's Alpha value of 0.87, indicating high reliability. These findings indicate that the application has good levels of usability, engagement, and user acceptance, and demonstrates the potential to support learning motivation and the effectiveness of mobile-based Mandarin vocabulary learning at the beginner level.